Ecology and genetic diversity of Gentiana pannonica populations in different geographical and habitat scales - Ekrtová, Ester (Jihočeská univerzita, 2013)
The thesis focused to population ecology and genetics of subalpine species Gentiana pannonica. Pollination ecology of species and generative reproduction in different habitat (primary vs. secondary) were investigated in the field. Genetic variation and structure of G. pannonica populations were studied in three disjunct parts of its distribution range: the Eastern Alps, the Bohemian Forest, and the Giant Mts. Present distribution of G. pannonica in the central past of the Bohemian Forest were processed.
Ecology and genetic diversity of Gentiana pannonica populations in different geographical and habitat scales
Ecology and genetic diversity of Gentiana pannonica populations in different geographical and habitat scales
Keywords: Gentiana pannonica; population biology; genetic diversity; rare species; the Bohemian Forest; the Alps; the Giant Mts.; Gentiana pannonica; population biology; genetic diversity; rare species; the Bohemian Forest; the Alps; the Giant Mts.